2016 XXII International Conference on Electrical Machines (ICEM) 2016
DOI: 10.1109/icelmach.2016.7732808
|View full text |Cite
|
Sign up to set email alerts
|

Structural design optimization of a high speed synchronous reluctance machine

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Abstract-Synchronous reluctance machines, including the permanent magnet assisted variants are competitive motor topologies if the application requires high efficiency and a cost effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Most similar approaches focus on active parts design, passive parts and geometries are often neglected, but can have a significant influence on certain optimization objectives (Golovanov et al, 2019). In (Di Nardo et al, 2016) a component specific design is reported for the design of a rotor for a synchronous reluctance motor. Here only parameters of this specific component are considered, thus fixing parameters of other machine components, e.g.…”
Section: Component Design In Mdda Of Electric Motorsmentioning
confidence: 99%
“…Most similar approaches focus on active parts design, passive parts and geometries are often neglected, but can have a significant influence on certain optimization objectives (Golovanov et al, 2019). In (Di Nardo et al, 2016) a component specific design is reported for the design of a rotor for a synchronous reluctance motor. Here only parameters of this specific component are considered, thus fixing parameters of other machine components, e.g.…”
Section: Component Design In Mdda Of Electric Motorsmentioning
confidence: 99%
“…Since this form of geometry simplification is limited when dealing with more complex geometries, FEA calculations tend to be used for this purpose in the reviewed papers. Thus, there are a variety of papers that use 2D FEA simulations to evaluate detailed rotor geometries in synchronous reluctance machines [44,68,83] and permanent magnet-excited machines [22,43,66,84]. For the design of high-speed rotors that include retention sleeves, 2D FEA is also utilized [50,60].…”
Section: Structural Mechanicsmentioning
confidence: 99%
“…Reference [104] presents and compares different architectures of coupled electromagnetic and mechanical analyses. Reference [83] suggests a parameter-split decoupling (PSD) approach, where the design parameters of a SynRM rotor are split into two subsets. One subset will be part of the electromagnetic analysis, with the other being fixed, and vice versa for the structural analysis.…”
Section: Domain Couplingsmentioning
confidence: 99%
“…The location and distribution of the iron ribs along the barriers need to be optimized keeping the total iron bridge thickness per barrier as close as possible to the analytical estimated values. By doing so, the average torque would not change being not affected by the ribs position along the barrier but mainly by their thickness [32].…”
Section: Optimal Machinesmentioning
confidence: 99%